The Effect of Game Analytical Game (Gag) Towards The Improvement of Soccer Dribbling Basic Technical Skill - Putra, Aldo Naza; Tangkudung, James; Hanif, Sofyan (Department of Physical Education, Sport, Health and Recreation, 2020)
To be able to play the soccer game well and achieve victory, a number of fundamental aspects should be mastered by every player, especially basic technical skills. Mastery of soccer basic technical skills is fundamental in the process of player development. The purpose of this study is to find out whether the soccer basic technical skills training model through the GAG approach is effective to improve the basic technical skills of soccer dribbling. The research method used is quantitative research with Quasi-Experiment. The design used is the pre test post test Non Equivalent Control Group Design. The subjects in this study were SSB students aged 6-9 years old. The results of this study are based on data analysis through an independent sample test, in which it was found that the sig (2-tailed) value is 0.000 < 0.05. It can be concluded that there is a significant (real) effectiveness difference between the use of the training model through the GAG approach and the conventional learning model to improve the soccer dribbling technique skills of SSB students aged 6-9 years old